Pangaranto Sailaon as an Expression in Karaya Music - Gabriella; Wimbrayardi (Universitas Negeri Padang, 2024)
Although Batak socio-cultural changes in overseas can be distinguished, they are difficult to separate. Change, social refers more to changes in structure, while cultural change is more oriented towards changes in the thinking system of the community. Given that human life is shrouded in culture, culture itself is created and developed in social life. Therefore, cultural change is not something that needs to be mourned or prevented. Cultural change must be observed in terms of meeting the needs of the Batak community itself, so cultural change will always take place, along with social changes themselves. From the idea of composite cultivation the author does not talk about the course of events about Batak culture assimilating with other cultures, because each ethnicity has its own identity and characteristics, but provides one of the offers in sound language to express the expression of